The human resources crisis in South Africa: Challenges and opportunities for business - F. Grant Schutte (South African Journal of Business Management, 1982)
In view of the importance of the human asset to the South African economy, the major crises facing South African managers in the human resources area are discussed, together with possible solutions to these problems. The six major components of the human resources crisis, as perceived by the author, are related in a matrix to 11 major challenges or opportunities for management, in the handling of these problems. The crisis components discussed are: actual and potential large-scale black unemployment; a shortage of skilled and semi-skilled labour; a shortage of supervisory and middle management; socio-political wage pressure; strikes; and problems relating to cultural differences. The challenges facing business include: the promotion of entrepreneurship; developing greater understanding of cultural differences; development and retraining; skills training; selling the free enterprise system; the creation of jobs; effective delegation, communication, control and feedback; improved union negotiation; improved industrial relations; increased productivity; and the development of strategies and plans to prevent a greater crisis.
Keywords: 650